The Role of Metacognition Strategies (Metacomprehension) and Inferential Ability in Improving Reading Comprehension Ability - Hendaryan; Noviadi, Andri (Universitas Muhammadiyah Malang, 2023)
This research was motivated by the low reading comprehension ability of junior high school students in the field. The purpose of this research is to investigate the role of metacognition strategies and inferential abilities in improving students' reading comprehension abilities. The method used is a quasi-experiment with the aim of looking at the role of inferential abilities and metacognitive abilities in improving reading comprehension abilities. Apart from that, this research also uses correlational methods to study the relationship between these three variables (metacognitive components, inferential abilities, and reading comprehension abilities). The participants involved in this research were 300 junior high school students taken from 8 schools in the Ciamis area. Samples are selected randomly. Research findings show that metacognitive strategies are able to significantly improve students' reading comprehension skills through the stages of planning, monitoring, and evaluating. The reading comprehension skills possessed by these students are able to help them provide predictions of reading content with a good level of accuracy. The integration of components in metacognitive strategies and inferential abilities can improve reading comprehension abilities, especially inferential reading abilities. This research has the implication that teachers must optimize students' inferential abilities through metacognitive strategies so that students' reading comprehension abilities can also increase significantly.